“Depois que eu releio, eu continuo escrevendo”: as relações entre os processos metacognitivos e a produção textual de crianças no ciclo de alfabetização - Brilhante, Luiza Hermínia de Almeida Assis (2021)
The aim is, in general, to investigate the relations between the development of metacognitive processes and the textual production of children throughout the literacy cycle. The specific objectives aim to: 1- Verify, throughout the literacy cycle, how metacognitive knowledge and its possible evolutions were manifested during the textual production of children in a common classroom context. 2- Identify the metacognitive strategies used by these children when producing texts written in the literacy cycle. 3- Examine which factors of textuality are considered by children in their written productions throughout the literacy cycle. 4- Analyze how metacognitive knowledge and strategies contribute to the textuality of children’s written productions throughout the literacy cycle. It is based on the psycholinguistic perspective of written language, studies on Metacognition, Textual Production and Didactic Sequence with Textual Genres, as well as references on textuality. The methodology comprises a participatory research, with the construction of data in a longitudinal way, starting the monitoring of children in the 1st grade of E.S until the conclusion of the cycle in the 2nd grade of E.S. The procedures consist of observation, identification of explanation and proposition of didactic sequences with textual genres in the classroom. An interpretative microanalysis was performed to describe the child’s interactions in the textual production activity, identifying the development of metacognitive processes through the writing of texts and their relations with the qualification of textual productions written in the literacy cycle.